Descripción física del plasma de un sistema de espectroscopía LIBS y su aplicación a la detección de cadmio y plomo en muestras de suelo - Lay Mesones, Enrique Javier (2024)
This thesis describes the plasma generated by the laser-induced breakdown spectroscopy (LIBS) technique and its application to the detection of cadmium and lead in soil samples. It addresses the laser-sample interaction, plasma formation, radiation emission, material ablation, and the local thermodynamic equilibrium model. A protocol is developed to prepare standards in soil samples with known concentrations of cadmium (50-1000 ppm) and lead (1000 -10 000 ppm). The samples, extracted from the gardens of the Physics section at the Pontifical Catholic University of Peru, are dried, crushed, pulverized, VLHYHG HQULFKHGZLWK&G&Oၷā+ၷ2DQG3E 12ၸ ၷVROXWLRQV DQGSUHVVHGLQWRSHOOHWV The experimental setup includes a pulsed laser, an optical system, a spectrometer, electronic synchronization, and a rotating support that allows each pulse to hit a different area and generate a LIBS spectrum. Emission lines of cadmium (214,439 nm, 226,502 nm, and 228,802 nm) and lead (405,708 nm) are identified, as well as others from iron, magnesium, calcium, aluminum, silicon, and titanium. From the spectra, the first 150 are discarded, and outlier removal techniques are applied: one based on the median absolute deviation for lead pellets and another using the Mahalanobis distance for cadmium pellets. Calibration curves are created with the intensities and areas under the emission lines, reporting coefficients of determination close to one and low detection and quantification limits. The methodology shows good repeatability and variable matrix effects for different samples. Finally, the results are validated with atomic absorption spectroscopy.